Impure Procedural Justice in Climate Governance Systems. (December 2015) - Grasso, Marco; Sacchi, Simona
Climate change governance is extremely challenging because of both the intrinsic difficulty of the issues at stake and the plurality of values and world-views. For these reasons, the ethical concerns that characterise climate change should also be meaningfully addressed through a specific version of procedural justice. Accordingly, in this article we adopt an impure notion of procedural justice. On this theoretical basis, we define relevant fairness criteria and contextualise them for climate governance systems. Then, we empirically justify fairness criteria against a critical and divisive element for the future governance of the Green Climate Fund, i.e., the no-objection procedure. The article concludes with some considerations prompted by the analysis.